Dangerous women [compact disc, unabridged] - Penzler, Otto; Archer, Ellen (Narrator); Lawlor, Patrick G. (Patrick Girard); Prichard, Michael (Michael J.); Vance, Simon; Sklar, Alan (Tantor Media, 2005)
A collection of short tales about dangerous women, written by top suspense authors, includes pieces by Nelson DeMille, J.A. Jance, and Elmore Leonard.